Prenatal Diagnosis of Sacrococcygeal Teratoma Using Two and Three-Dimensional Ultrasonography - Livia Teresa Moreira Rios; Edward Araujo Júnior; Luciano Marcondes Machado Nardozza; Antonio Fernandes Moron; Marília da Glória Martins (Case Reports in Obstetrics and Gynecology)
Sacrococcygeal teratoma accounts for half of all fetal tumors, with a prevalence of 1 : 40,000 births. It is believed to originate from pluripotent cells in Hensen's nodule. Although most are benign, they are associated with high morbidity and mortality rates because the fetus develops congestive heart failure and hydrops. Factors leading to poor prognosis include solid components in the mass, and hydrops diagnosed before the 30th week. A case of prenatal sacrococcygeal teratoma diagnosed using B-mode and color Doppler two-dimensional ultrasonography (2DUS) is described, in which three-dimensional ultrasonography (3DUS) enabled characterization of the extent of fetal lesions and allowed the parents to understand the pathological condition better. A 20-year-old primigravida was referred with a solid mass diagnosed in the lumbosacral spine. Examinations performed at our institution revealed pregnancy of 23 weeks and 4 days, with a female fetus presenting a bulky solid mass with cystic components and calcifications, measuring 7.7×9.1×12.2 cm, starting from the sacral region, with internal flow seen on color Doppler. A new ultrasound confirmed fetal death at 25 weeks and 4 days. Postnatal findings confirmed the diagnosis of sacrococcygeal teratoma. 3DUS can be used in cases of sacrococcygeal teratoma to assess the development of tumor during the prenatal and to allow better understanding of this anomaly by the parents.